The development of a research framework for inventory performance improvement of the automotive manufacturing industry: review of literature from 2011-2020 - Manoharan Murugeson; Mohd Nazri Mohd Noor; Arumugam G Sithamparam (2023)
The main purpose of this study is to examine existing literature on how inventory performance in the automotive manufacturing supply chain can be improved. Articles reviewed are from the last ten years that is related to automotive manufacturing industry and targeted to inventory performance. Transformational changes are happening in the automotive manufacturing supply chains with ubiquitous technology leading the transformation. Inherently, due to its outsourced manufacturing in dispersed locations globally, communication and coordination would be affected in some form. This results in companies in the automotive manufacturing supply chain resorting to hold more inventory to mitigate the uncertainty. Therefore, to address this issue, this study conceptualises a theoretical framework that is adapted from Galbraith’s (1974) Organisational Information Processing Theory. The recommended framework may provide a guide to practitioners on understanding the intricacies of supply chain integration and how technology tools may help in mitigating risks and improve inventory performance (Abstract by authors)